FILSAFAT PENDIDIKAN YANG MEMBEBASKAN DALAM PERSPEKTIF PENDIDIKAN ISLAM - Samsul Bahri (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2017)
This paper examines the liberating philosophy of education in the perspective of Islamic education. The method used is descriptive-analytical with historical approach. This study found that liberation education philosophy became a mission in the world of Islamic education and has occurred in the time of the Prophet Muhammad until the golden age of Islam. However, after the decline of the Islamic world until now virtually a dichotomous virus has occurred, even liberation education philosophy no longer occurs in the world of Islamic education. Therefore, Islamic education should be able to be a means of liberation to prepare learners to plunge in people's lives. In addition, the dichotomy of science should be abolished by the view that science is all derived from Islam. Liberate education will be realized if Islamic education is willing to reorient: Having a clear vision, mission, and strategic orientation. Strong social, intellectual and moral legitimacy.to the society and respond to the demands of the era Managed with modern management that is professional, rational, open, accountable, humanist, has access, cooperation and global partnership.